Diagnosis disclosure, medication hiding, and medical functioning among perinatally infected, HIV-positive children and adolescents. - Calabrese, Sarah K; Martin, Staci; Wolters, Pamela L; Toledo-Tamula, Mary A; Brennan, Tara L; Wood, Lauren V (AIDS care, 2012)
Little is known about the immunological and virological impact of diagnosis disclosure among HIV-positive children and adolescents. The current cross-sectional study examined medication hiding as a mediator of the relationship between disclosure to friends and three medical outcomes: CD4+ absolute count, CD4+ percentage, and viral load. Participants included 25 perinatally infected, HIV-positive children and adolescents ages 11-18 years from the US. Diagnosis disclosure and medication hiding were self-reported by participants and medical markers were derived from blood samples drawn during the same clinic visit. Bootstrapping analyses revealed that disclosure to at least one friend (versus no friends) was associated with less medication hiding, which was associated with higher CD4+ absolute counts and percentages but not viral load. Further, among the subset of participants who had disclosed to at least one friend (n = 19), those who reported disclosing to 11 or more versus 1-10 friends were less likely to hide medication taking, which was associated with higher CD4+ absolute counts. Findings suggest HIV-positive children and adolescents' diagnosis disclosure to friends corresponds to less medication hiding, ultimately yielding better immune functioning. Health care providers should be cognizant of these potential medical benefits associated with disclosure when offering support around disclosure decision-making.
Keywords: Adolescent; Antiretroviral Therapy, Highly Active; CD4 Lymphocyte Count; Child; Cross-Sectional Studies; Female; HIV Infections; Humans; Male; Peer Group; Self Disclosure; Self Report; Treatment Outcome; United States; Viral Load